The Paradox of ‘Water Is Life’ in a Water Rationed City During the COVID-19 Pandemic - Tavengwa Chitata; Tirivashe Philip Masere; Bester Tawona Mudereri; Blessing Mirika Ndau; Solomon Farai Zirebwa; Batanai Lovemore Sammie; Rangarirayi Lucia Mhindu; Ngonidzashe Lewis Mufute; Kudakwashe Makwena; Dzikamai Chipunza; Joy Mufaro Sibanda; Augustine Mureri; et al. (Springer Link, 2023)
Abstract